A characterisation of the geothermal potential of the Muschelkalk deposits’ location, with the prospective of its utilization in balneology and recreation (southern Poland) - Gancarz, Marzena (Geology, Geophysics and Environment, 2016)
Analysis of geothermal potential of the Muschelkalk deposits was carried out from the point of view of utilising hot groundwater in balneology and recreation. As a result of a number of analytical studies, the area situated in the southern part of the Polish Lowland was selected as one of prospective areas for the location of geothermal intakes. This area encompasses a southern part of the Fore-Sudetic Monocline, a southern part of the Łódź Trough, and a small section of the Miechowska Trough. The deposits are buried at depths of between 500 m b.s.l and 1500 m b.s.l., their thicknesses are from 100 m to 300 m, the temperature at the top in most cases is about 30 - 50 °C, TDS in most cases does not exceed 60 g/dm³, mineralised water flood tide is from 0.4 m³/h to 13.8 m³/h, porosity is between 9 % and 23 %, and permeability is from 25 mD to 340 mD.As a result of the analyses, the most favourable conditions for development of balneotherapy and recreation in the Muschelkalk deposits in the three locations of the selected area were found to be where the boreholes Trzebnica IG- 1 (first area), Wierzchlas 3, Rzeki IG- 1 (second area), and Trzonów 2 (third area), were located.